3D Nanoscale Mapping of Short‐Range Order in GeSn Alloys. Issue 5 (3rd April 2022) - Liu, Shang; Covian, Alejandra Cuervo; Wang, Xiaoxin; Cline, Cory T.; Akey, Austin; Dong, Weiling; Yu, Shui‐Qing; Liu, Jifeng
Abstract: GeSn on Si has attracted much research interest due to its tunable direct bandgap for mid‐infrared applications. Recently, short‐range order (SRO) in GeSn alloys has been theoretically predicted, which profoundly impacts the band structure. However, characterizing SRO in GeSn is challenging. Guided by physics‐informed Poisson statistical analyses of k ‐nearest neighbors (KNN) in atom probe tomography (APT), a new approach is demonstrated here for 3D nanoscale SRO mapping and semi‐quantitative strain mapping in GeSn. For GeSn with ≈14 at. % Sn, the SRO parameters of Sn–Sn 1NN in 10 × 10 × 10 nm 3 nanocubes can deviate from that of the random alloys by ±15 %. The relatively large fluctuation of the SRO parameters contributes to band‐edge softening observed optically. Sn–Sn 1NN also tends to be more favored toward the surface, less favored under strain relaxation or tensile strain, while almost independent of local Sn composition. An algorithm based on least square fit of atomic positions further verifies this Poisson‐KNN statistical method. Compared to existing macroscopic spectroscopy or electron microscopy techniques, this new APT statistical analysis uniquely offers 3D SRO mapping at nanoscale resolution in a relatively large volume with millions of atoms. It can also be extended to investigate SRO in other alloy systems. Abstract : Guided by Poisson statistical analyses of k ‐nearest neighbors (KNN) in atom probe tomography, a new approach is demonstrated for 3D nanoscale short‐range order (SRO) mapping in Ge0.86 Sn0.14 . The fluctuation of the SRO contributes to band‐edge softening. Sn–Sn 1NN tends to be more favored toward surface, less favored under strain relaxation or tensile strain, while almost independent of local Sn composition.